(untitled) (Journal of Atomic and Molecular Sciences, 2012)
Detailed calculations for electron impact ionization including direct ionization (DI) and excitation autoionization (EA) processes along the ground-state Be-like rare gas ions have been performed by using relativistic distorted wave (RDW) approximation. The DI contribution from 2s shell and the EA contributions from inner-shell electron impact excitations of 1s-nl (n≤ 12, l ≤ 4) were considered. The contribution of DI is a little more than 90% to the total electron impact ionization cross section. The main EA contribution comes from 1s-2p electron impact excitation channel. The EA contribution relative to DI contribution first increased and then decreased as the atomic number Z increases in Be-like rare gas ion. The EA rate coefficients are given for all ground-state Be-like rare gas ions as a function of impact electron temperature.